Analysis of molecular mechanisms of 5-fluorouracil-induced steatosis and inflammation in vitro and in mice - Sommer, Judith; Mahli, Abdo; Freese, Kim; Schiergens, Tobias S.; Kuecuekoktay, Fulya Suzan; Teufel, Andreas; Thasler, Wolfgang E.; Mueller, Martina; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Oncotarget, 2017)
Chemotherapy-associated steatohepatitis is attracting increasing attention because it heralds an increased risk of morbidity and mortality in patients undergoing surgery because of liver metastases. The aim of this study was to develop in vitro and in vivo models to analyze the pathogenesis of 5-fluorouracil (5-FU)-induced steatohepatitis.Therefore, primary human hepatocytes and HepG2 hepatoma cells were incubated with 5-FU at non-toxic concentrations up to 24 h. Furthermore, hepatic tissue of C57BL/6N mice was analyzed 24 h after application of a single 5-FU dose (200 mg/kg body weight). In vitro, incubation with 5-FU induced a significant increase of hepatocellular triglyceride levels. This was paralleled by an impairment of mitochondrial function and a dose- and time-dependently increased expression of fatty acid acyl-CoA oxidase 1 (ACOX1), which catalyzes the initial step for peroxisomal ?-oxidation. The latter is known to generate reactive oxygen species, and consequently, expression of the antioxidant enzyme heme oxygenase 1 (HMOX1) was significantly upregulated in 5-FU-treated cells, indicative for oxidative stress. Furthermore, 5-FU significantly induced c-Jun N-terminal kinase (JNK) activation and the expression of pro-inflammatory genes IL-8 and ICAM-1. Also in vivo, 5-FU significantly induced hepatic ACOX1 and HMOX1 expression as well as JNK-activation, pro-inflammatory gene expression and immune cell infiltration. In summary, we identified molecular mechanisms by which 5-FU induces hepatocellular lipid accumulation and inflammation. Our newly developed models can be used to gain further insight into the pathogenesis of 5-FU-induced steatohepatitis and to develop therapeutic strategies to inhibit its development and progression.
EVALuna2:4753

Bone Morphogenetic Protein-8B Expression is Induced in Steatotic Hepatocytes and Promotes Hepatic Steatosis and Inflammation In Vitro - Mahli, Abdo; Seitz, Tatjana; Beckroege, Tobias; Freese, Kim; Thasler, Wolfgang Erwin; Benkert, Matthias; Dietrich, Peter; Weiskirchen, Ralf; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cells, 2019)
Non-alcoholic fatty liver disease (NAFLD) is considered to be the hepatic manifestation of the metabolic syndrome. The bone morphogenetic protein-8B (BMP8B) has been shown to be expressed in brown adipose tissues and the hypothalamus and to affect thermogenesis and susceptibility to diet-induced obesity. Here, we aimed to analyze BMP8B expression in NAFLD and to gain insight into BMP8B effects on pathophysiological steps of NAFLD progression. BMP8B mRNA and protein expression were dose-dependently induced in primary human hepatocytes in vitro upon incubation with fatty acids. Furthermore, hepatic BMP8B expression was significantly increased in a murine NAFLD model and in NAFLD patients compared with controls. Incubation with recombinant BMP8B further enhanced the fatty acid-induced cellular lipid accumulation as well as NFB activation and pro-inflammatory gene expression in hepatocytes, while siRNA-mediated BMP8B depletion ameliorated these fatty acid-induced effects. Analysis of the expression of key factors of hepatocellular lipid transport and metabolisms indicated that BMP8B effects on fatty acid uptake as well as de novo lipogenesis contributed to hepatocellular accumulation of fatty acids leading to increased storage in the form of triglycerides and enhanced combustion by beta oxidation. In conclusion, our data indicate that BMP8B enhances different pathophysiological steps of NAFLD progression and suggest BMP8B as a promising prognostic marker and therapeutic target for NAFLD and, potentially, also for other chronic liver diseases.
CRIS-Team WoS Importer:2019-06-28

Combined effects of PLK1 and RAS in hepatocellular carcinoma reveal rigosertib as promising novel therapeutic "dual-hit" option - Dietrich, Peter; Freese, Kim; Mahli, Abdo; Thasler, Wolfgang Erwin; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Oncotarget, 2018)
Inhibition of RAS-RAF-ERK-signaling is a major mechanism mediated by the multi-kinase inhibitors sorafenib and regorafenib, the only effective therapeutic approaches for advanced hepatocellular carcinoma (HCC). This underlines the importance of RAS-RAF-ERK-signaling in HCC. Most RAS isoforms were not yet described to play crucial roles in HCC. However, several studies indicate that the HRAS isoform can function as potent oncogene in HCC, but pharmacologic RAS inhibition has not yet been investigated. Moreover, the cell cycle promoting polo-like kinase 1 (PLK1) is an increasingly recognized therapeutic target in HCC that can be activated by RAS-RAF-signaling. A recently developed small molecule inhibitor, ON-01910 ("rigosertib", RGS), was shown to interfere with both RAS- and PLK1-signaling. The aim of this study was to analyze the effects of RGS in HCC and to assess PLK1 and HRAS expression in HCC. RGS treatment reduced cell proliferation and induced cell cycle arrest in human HCC cell lines in vitro. Moreover, RGS strongly inhibited both ERK- and AKT-activation in HCC cells, indicating disruption of RAS-signaling. Analysis of HCC patient data showed that PLK1 and HRAS expression levels are upregulated during HCC development and in advanced HCC, respectively. High expression levels of PLK1 significantly correlated with poor patient survival. Moreover, high expression of both PLK1 and HRAS revealed combined effects on patient outcome. This underscores the importance of these genes and associated pathways in HCC. We newly demonstrate the therapeutic potential of RGS in HCC by inhibition of both PLK1 activation and major RAS-pathways, revealing a novel therapeutic "dual-hit" approach for HCC.
EVALuna2:34067

Fibroblast Growth Factor 9 is expressed by activated hepatic stellate cells and promotes progression of hepatocellular carcinoma - Seitz, Tatjana; Freese, Kim; Dietrich, Peter; Thasler, Wolfgang Erwin; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Scientific Reports, 2020)
Hepatocellular carcinoma (HCC) is closely associated with liver fibrosis. Hepatic stellate cells (HSC) and cancer-associated myofibroblasts are key players in liver fibrogenesis and hepatocarcinogenesis. Overexpression of fibroblast growth factor (FGF) receptors contributes to HCC development and progression. This study aimed to elucidate the role of FGFs in the HSC-HCC crosstalk. Analysis of the expression of the fifteen paracrine FGF-members revealed that FGF9 was only expressed by HSC but not by HCC cells. Also in human HCC tissues, HSC/stromal myofibroblasts were identified as cellular source of FGF9. High expression levels of FGF9 significantly correlated with poor patient survival. Stimulation with recombinant FGF9 induced ERK- and JNK-activation combined with significantly enhanced proliferation, clonogenicity, and migration of HCC cells. Moreover, FGF9 significantly reduced the sensitivity of HCC cells against sorafenib. Protumorigenic effects of FGF9 on HCC cells were almost completely abrogated by the FGFR1/2/3 inhibitor BGJ398, while the selective FGFR4 inhibitor BLU9931 had no significant effect. In conclusion, these data indicate that stroma-derived FGF9 promotes tumorigenicity and sorafenib resistance of HCC cells and FGF9 overexpression correlates with poor prognosis in HCC patients. Herewith, FGF9 appears as potential prognostic marker and novel therapeutic target in HCC.
CRIS-Team Scopus Importer:2020-03-27

Four-And-A-Half LIM-Domain Protein 2 (FHL2) Deficiency Aggravates Cholestatic Liver Injury - Sommer, Judith; Dorn, Christoph; Gaebele, Erwin; Bataille, Frauke; Freese, Kim; Seitz, Tatjana; Thasler, Wolfgang E.; Buettner, Reinhard; Weiskirchen, Ralf; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cells, 2020)
Cholestasis occurs in different clinical circumstances and leads to severe hepatic disorders. The four-and-a-half LIM-domain protein 2 (FHL2) is a scaffolding protein that modulates multiple signal transduction pathways in a tissue- and cell context-specific manner. In this study, we aimed to gain insight into the function of FHL2 in cholestatic liver injury. FHL2 expression was significantly increased in the bile duct ligation (BDL) model in mice. In Fhl2-deficient (Fhl2-ko) mice, BDL caused a more severe portal and parenchymal inflammation, extended portal fibrosis, higher serum transaminase levels, and higher pro-inflammatory and pro-fibrogenic gene expression compared to wild type (wt) mice. FHL2 depletion in HepG2 cells with siRNA resulted in a higher expression of the bile acid transporter Na+-taurocholate cotransporting polypeptide (NTCP) gene. Furthermore, FHL2-depleted HepG2 cells showed higher expression of markers for oxidative stress, lower B-cell lymphoma 2 (Bcl2) expression, and higher Bcl2-associated X protein (BAX) expression after stimulation with deoxycholic acid (DCA). In hepatic stellate cells (HSCs), FHL2 depletion caused an increased expression of TGF-β and several pro-fibrogenic matrix metalloproteinases. In summary, our study shows that deficiency in FHL2 aggravates cholestatic liver injury and suggests FHL2-mediated effects on bile acid metabolisms and HSCs as potential mechanisms for pronounced hepatocellular injury and fibrosis.
EVALuna2:212289

Histone deacetylase expressions in hepatocellular carcinoma and functional effects of histone deacetylase inhibitors on liver cancer cells in vitro - Freese, Kim; Seitz, Tatjana; Dietrich, Peter; Lee, Serene M.L.; Thasler, Wolfgang E.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cancers, 2019)
Hepatocellular carcinoma (HCC) is a leading cause for deaths worldwide. Histone deacetylase (HDAC) inhibition (HDACi) is emerging as a promising therapeutic strategy. However, most pharmacological HDACi unselectively block different HDAC classes and their molecular mechanisms of action are only incompletely understood. The aim of this study was to systematically analyze expressions of different HDAC classes in HCC cells and tissues and to functionally analyze the effect of theHDACisuberanilohydroxamic acid (SAHA) and trichostatinA(TSA) on the tumorigenicity of HCC cells. The gene expression of all HDAC classes was significantly increased in human HCC cell lines (Hep3B, HepG2, PLC, HuH7) compared to primary human hepatocytes (PHH). The analysis of HCC patient data showed the increased expression of several HDACs in HCC tissues compared to non-tumorous liver. However, there was no unified picture of regulation in three different HCC patient datasets and we observed a strong variation in the gene expression of different HDACs in tumorous as well as non-tumorous liver. Still, there was a strong correlation in the expression of HDAC class IIa (HDAC4, 5, 7, 9) as well as HDAC2 and 8 (class I) and HDAC10 (class IIb) and HDAC11 (class IV) in HCC tissues of individual patients. This might indicate a common mechanism of the regulation of these HDACs in HCC. The Cancer Genome Atlas (TCGA) dataset analysis revealed that HDAC4, HDAC7 and HDAC9 as well as HDAC class I members HDAC1 and HDAC2 is significantly correlated with patient survival. Furthermore, we observed that SAHA and TSA reduced the proliferation, clonogenicity and migratory potential of HCC cells. SAHA but not TSA induced features of senescence in HCC cells. Additionally, HDACi enhanced the efficacy of sorafenib in killing sorafenib-susceptible cells. Moreover, HDACi reestablished sorafenib sensitivity in resistant HCC cells. In summary, HDACs are significantly but differently increased in HCC, which may be exploited to develop more targeted therapeutic approaches. HDACi affect different facets of the tumorigenicity of HCC cells and appears to be a promising therapeutic approach alone or in combination with sorafenib.
CRIS-Team Scopus Importer:2019-11-22
Keywords: Hepatocellular carcinoma; Histone deacetylase; Histone deacetylase inhibitor; Sorafenib

Intestinal fungi contribute to development of alcoholic liver disease - Yang, An-Ming; Inamine, Tatsuo; Hochrath, Katrin; Chen, Peng; Wang, Lirui; Llorente, Cristina; Bluemel, Sena; Hartmann, Phillipp; Xu, Jun; Koyama, Yukinori; Kisseleva, Tatiana; Torralba, Manolito G.; et al. (Journal of Clinical Investigation, 2017)
Chronic liver disease with cirrhosis is the 12th leading cause of death in the United States, and alcoholic liver disease accounts for approximately half of all cirrhosis deaths. Chronic alcohol consumption is associated with intestinal bacterial dysbiosis, yet we understand little about the contribution of intestinal fungi, or mycobiota, to alcoholic liver disease. Here we have demonstrated that chronic alcohol administration increases mycobiota populations and translocation of fungal ?-glucan into systemic circulation in mice. Treating mice with antifungal agents reduced intestinal fungal overgrowth, decreased ?-glucan translocation, and ameliorated ethanol-induced liver disease. Using bone marrow chimeric mice, we found that ?-glucan induces liver inflammation via the C-type lectin-like receptor CLEC7A on Kupffer cells and possibly other bone marrow-derived cells. Subsequent increases in IL-1? expression and secretion contributed to hepatocyte damage and promoted development of ethanol-induced liver disease. We observed that alcohol-dependent patients displayed reduced intestinal fungal diversity and Candida overgrowth. Compared with healthy individuals and patients with non-alcohol-related cirrhosis, alcoholic cirrhosis patients had increased systemic exposure and immune response to mycobiota. Moreover, the levels of extraintestinal exposure and immune response correlated with mortality. Thus, chronic alcohol consumption is associated with an altered mycobiota and translocation of fungal products. Manipulating the intestinal mycobiome might be an effective strategy for attenuating alcohol-related liver disease.
EVALuna2:4754

Therapeutic Application of Micellar Solubilized Xanthohumol in a Western-Type Diet-Induced Mouse Model of Obesity, Diabetes and Non-Alcoholic Fatty Liver Disease - Mahli, Abdo; Seitz, Tatjana; Freese, Kim; Frank, Jan; Weiskirchen, Ralf; Abdel-Tawab, Mona; Behnam, Dariush; Hellerbrand, Claus (Cells, 2019)
Xanthohumol (XN), a prenylated chalcone from hops, has been reported to exhibit a variety of health-beneficial effects. However, poor bioavailability may limit its application in the prevention and therapy of diseases. The objective of this study was to determine whether a micellar solubilization of xanthohumol could enhance the bioavailability and biological efficacy of xanthohumol in a Western-type diet (WTD) induced model of obesity, diabetes and non-alcoholic fatty liver disease (NAFLD). After 3 weeks feeding with WTD, XN was additionally applied per oral gavage as micellar solubilizate (s-XN) or native extract (n-XN) at a daily dose of 2.5 mg/kg body weight for a further 8 weeks. Control mice received vehicle only in addition to the WTD. WTD-induced body weight-gain and glucose intolerance were significantly inhibited by s-XN application. Furthermore, WTD-induced hepatic steatosis, pro-inflammatory gene expression (MCP-1 and CXCL1) and immune cell infiltration as well as activation of hepatic stellate cells (HSC) and expression of collagen alpha I were significantly reduced in the livers of s-XN-treated mice compared to WTD controls. In contrast, application of n-XN had no or only slight effects on the WTD-induced pathological effects. In line with this, plasma XN concentration ranged between 100-330 nmol/L in the s-XN group while XN was not detectable in the serum samples of n-XN-treated mice. In conclusion, micellar solubilization enhanced the bioavailability and beneficial effects of xanthohumol on different components of the metabolic syndrome including all pathological steps of NAFLD. Notably, this was achieved in a dose more than 10-fold lower than effective beneficial doses of native xanthohumol reported in previous in vivo studies.
CRIS-Team WoS Importer:2019-06-18

Variation of different histone deacetylases and the functional effects of HDAC inhibitors in hepatocellular carcinoma - Freese, Kim; Dietrich, Peter; Boßerhoff, Anja Katrin; Hellerbrand, Claus (JOURNAL OF HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-05-07

Xanthohumol, a prenylated chalcone derived from hops, inhibits growth and metastasis of melanoma cells - Seitz, Tatjana; Hackl, Christina; Freese, Kim; Dietrich, Peter; Mahli, Abdo; Thasler, Reinhard Manfred; Thasler, Wolfgang Erwin; Lang, Sven Arke; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cancers, 2021)
Melanoma is one of the most aggressive and lethal cancers worldwide. Despite recent progress in melanoma therapy, the prognosis for metastasized melanoma continues to be poor. Xan-thohumol (XN), a prenylated chalcone derived from hop cones, is known to possess a broad spectrum of chemopreventive and anticancer activities. However, few studies have analyzed functional XN effects on melanoma cells and there have been no previous in vivo studies of its effects on metastasis. The aim of this study was to investigate the impact of XN on the tumorigenic and liver metastatic activity of melanoma cells. XN exhibited dose-dependent cytotoxic effects on human melanoma cell lines (Mel Ju; Mel Im) in vitro. Functional analysis in the subtoxic dose-range revealed that XN dose-dependently inhibited proliferation, colony formation, and migratory activity of melanoma cells. Subtoxic XN doses also induced markers of endoplasmic reticulum stress but inhibited the phosphorylation of the protumorigenic c-Jun N-terminal kinases (JNK). Furthermore, XN effects on hepatic metastasis were analyzed in a syngeneic murine model (splenic injection of murine B16 melanoma cells in C57/BL6 mice). Here, XN significantly reduced the formation of hepatic metastasis. Metastases formed in the liver of XN-treated mice revealed significantly larger areas of central necrosis and lower Ki67 expression scores compared to that of control mice. In conclusion, XN inhibits tumorigenicity of melanoma cells in vitro and significantly reduced hepatic metastasis of melanoma cells in mice. These data, in conjunction with an excellent safety profile that has been confirmed in previous studies, indicate XN as a promising novel agent for the treatment of hepatic (melanoma) metastasis.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Melanoma; Metastasis; Xanthohumol